Save Our Animals! | Blue Whale - Louise A Spilsbury; Richard Spilsbury (Chicago, IL, United States Heinemann Educational Books, 2006)
Introduces the characteristics and habitat of blue whales before describing the actions that threaten their existence and explaining how these animals can be saved.
Keywords: Life on Land; Non Fiction